2021
DOI: 10.3390/metabo11070463
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Relationship between the Cardiorespiratory Fitness and Plasma Metabolite Patterns in Healthy Humans—Results of the KarMeN Study

Abstract: Cardiorespiratory fitness (CRF) represents a strong predictor of all-cause mortality and is strongly influenced by regular physical activity (PA). However, the biological mechanisms involved in the body’s adaptation to PA remain to be fully elucidated. The aim of this study was to systematically examine the relationship between CRF and plasma metabolite patterns in 252 healthy adults from the cross-sectional Karlsruhe Metabolomics and Nutrition (KarMeN) study. CRF was determined by measuring the peak oxygen up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
(123 reference statements)
3
5
0
Order By: Relevance
“…A metabolic stimulus is probably missing here, as these patients are usually very inactive [ 22 ]. An association of PC aa C42:0 with cardiopulmonary fitness has already been shown for women in the KarMeN Study [ 23 ], which strengthens the assumption that it is a cross-gender marker of cardiopulmonary fitness.…”
Section: Discussionsupporting
confidence: 70%
“…A metabolic stimulus is probably missing here, as these patients are usually very inactive [ 22 ]. An association of PC aa C42:0 with cardiopulmonary fitness has already been shown for women in the KarMeN Study [ 23 ], which strengthens the assumption that it is a cross-gender marker of cardiopulmonary fitness.…”
Section: Discussionsupporting
confidence: 70%
“…Since leptin levels have been positively correlated to body fat percentage [ 28 , 29 ], the difference in leptin presumably results from a significant difference in body fat percentage between high-fit and low-fit females, further underpinning the validity of our data. Our observation that all other biomarkers and metabolic parameters were similar between the two groups, while previous studies in high and low aerobically fit individuals found significant differences in e.g., lipid and protein metabolites [ 30 , 31 , 32 , 33 , 34 , 35 ], is likely related to our standardised experimental set-up, as compared to other studies. We studied healthy, young-adult females of similar age and BMI in a highly controlled setting, while previous studies were performed with metabolically impaired individuals [ 26 ], and individuals with substantially different BMIs [ 30 , 31 , 32 , 35 ], or wider age ranges [ 30 , 35 ] in experimental conditions that were less standardised [ 30 , 31 , 32 , 33 , 35 ], and these factors especially impact circulating metabolite levels [ 26 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 42%
“…Our observation that all other biomarkers and metabolic parameters were similar between the two groups, while previous studies in high and low aerobically fit individuals found significant differences in e.g., lipid and protein metabolites [ 30 , 31 , 32 , 33 , 34 , 35 ], is likely related to our standardised experimental set-up, as compared to other studies. We studied healthy, young-adult females of similar age and BMI in a highly controlled setting, while previous studies were performed with metabolically impaired individuals [ 26 ], and individuals with substantially different BMIs [ 30 , 31 , 32 , 35 ], or wider age ranges [ 30 , 35 ] in experimental conditions that were less standardised [ 30 , 31 , 32 , 33 , 35 ], and these factors especially impact circulating metabolite levels [ 26 , 30 , 31 ]. Given that the levels of the analysed biomarkers and metabolic parameters were similar among the healthy females in our study, and multiple of these biomarkers and metabolic parameters showed dysregulation during disease, our findings imply that this biomarker and metabolic parameters set could be used to monitor progress from a healthy to an unhealthier state and may be used in health improvement interventions.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations